Learning-Related Brain-Electrical Activity Dynamics Associated with the Subsequent Impact of Learnt Action-Outcome Associations - Baum, Fabian; Wolfensteller, Uta; Ruge, Hannes (Frontiers in Human Neuroscience, 2017)
Goal-directed behavior relies on the integration of anticipated outcomes into action planning based on acquired knowledge about the current contingencies between behavioral responses (R) and desired outcomes (O) under specific stimulus conditions (S). According to ideomotor theory, bidirectional R-O associations are an integral part of this knowledge structure. Previous EEG studies have identified neural activity markers linked to the involvement of such associations, but the initial acquisition process has not yet been characterized. The present study thus examined brain-electrical activity dynamics during the rapid acquisition of novel bidirectional R-O associations during instructed S-R learning. Within a trial, we inspected response-locked and stimulus-locked activity dynamics in order to identify markers linked to the forward and backward activation of bidirectional R-O associations as they were being increasingly strengthened under forced choice conditions. We found that a post-response anterior negativity following auditory outcomes was increasingly attenuated as a function of the acquired association strength. This suggests that previously reported action-induced sensory attenuation effects under extensively trained free choice conditions can be established within few repetitions of specific R-O pairings under forced choice conditions¬. Furthermore, we observed the even more rapid development of a post-response but pre-outcome fronto-central positivity which was reduced for high R-O learners which might indicate the rapid deployment of preparatory attention towards predictable outcomes. Finally, we identified a learning-related stimulus-locked activity modulation within the visual P1-N1 latency range which might reflect the multi-sensory integration of the perceived antecedent visual stimulus and the anticipated auditory outcome.